Antimicrobial sensitivity of Listeria monocytogenes isolated from beef - Almeida, Rodolfo Nunes de; Universidade Federal do Ceará (2018)
The objective of this study was to investigate the antimicrobial susceptibility of Listeria monocytogenes previously isolated from beef. The experiment used ground beef, commercialized in the city of Uberaba, Minas Gerais, Brazil. Using the Kirby-Bauer method, analyzes of antimicrobial susceptibility were carried out in the 14 isolates of Listeria monocytogenes. All strains (100%) showed sensitivity to antimicrobials: amoxicillin, ampicillin, gentamicin, penicillin, teicoplanin and vancomycin; Six strains (42.86%) presented sensitivity to sulfamethoxazole / trimethoprim and tetracycline; 3 strains (21.43%) presented sensitivity to erythromycin and 2 strains (14.29%) showed sensitivity to ciprofloxacin. While 8 strains (57.14%) presented intermediate resistance to ciprofloxacin and tetracycline. All strains isolated showed resistance to cefazolin, cefepime, cefotaxime, clindamycin, oxacillin and polymyxin b. The antimicrobial resistance of Listeria monocytogenes poses serious risks to public health, due to its seriousness in affecting vulnerable segments of the human population, due to the wide presence of this bacterium in the environment, being isolated from food processing environments, water effluents to industries and causing possible contamination of various foodstuffs.